Carbon Biomass Algorithms Development for Mangrove Vegetation in Kemujan, Parang Island Karimunjawa National Park and Demak Coastal Area – Indonesia - Hartoko, Agus; Chayaningrum, Siska; Febrianti, Dewati Ayu; Ariyanto, Dafit; Suryanti (Procedia environmental sciences, 2015)
The increase and accumulation of greenhouse gases such as CO2 was believed had caused global warming. Effort to decrease accumulation these gases is by increasing the role of mangrove forests with its ecological function as carbon sinks through good management system. To this date, very limited study on the mangrove carbon biomass using satellite data espescially in tropical region. Purpose of the research were to calculate the carbon biomass of mangrove vegetation above ground through allometric equations, and to build spatial model algorithms of each mangrove species in the region by remote sensing technology using Quickbird, Geo Eye and ALOS satellite data. The research use an exploratory field survey and purposive sampling method and was performed through the measurement of trunk diameter (DBH) of above ground mangrove biomass without damaging vegetation (non-destructive sampling). About 21 mangrove species in Kemujan Island with total mangrove biomass above ground consist of the trunk, branches, leaves: 182.4 ton or 91.2 tons of Carbon, with largest carbon storage in the trunk. The results of spatial algorithms mangrove carbon biomass for Kemujan island using Quickbird data are Ceriops tagal with Y= - 0.003(B2/B3)2 + 0.267(B2/B3) – 3.452; Rhizophora apiculata with the algorithm Y= 0.001(B2/B3)2 - 0.116(B2/B3) + 3.415; Bruguiera cylindrical with the algorithm Y= - 0.003(B2/B3)2 + 0.336(B2/B3) – 7.265; Xylocarpus granatum with algorithm Y= 0.000(B2/B3)2 - 0.058(B2/B3) + 2.101; Rhizophora mucronata with the algorithm Y= 0.000(B2/B3)2 - 0.022(B2/B3) + 1.941. Mangrove carbon biomass algorithm using Geo Eye satellite data at Parang island for Rhizophora mucronata Y = -0.0436(B2/B3)2 + 0.526 (B2/B3) – 1.4642; Bruguiera gymnorrhiza Y = - 0.0027 (B2/B3)2 + 0.0649 (B2/B3) – 0.2432 and Bruguiera cylindrical Y = - 0.0089 (B2/B3)2 + 0.0632 (B2/B3) – 0.0683. Total mangrove carbon biomass at Demak coastal area range from 2.9 – 44.74 ton. Algorithm of mangrove carbon biomass at Demak using ALOS-AVNIR satellite data for Avicennia marina was Y = - 79.18 ((B1-B2)/(B1+B2))2 + 31.35 ((B1-B2)/(B1+B2)) - 1.191. The research concluded that band rationing of Band-2 with Band-3 for Quickbird and GeoEye data and Band-1 with Band-2 for ALOS data as the spectral signature of mangrove chlorophyll pigment with wave length of 0.5 - 0.6μm as the best for mangrove carbon algorithms.